(3QSGdI aj eYfi bhdge YbO GdhVY hYbO GdMed hGdJQcjH GdJbjjOi hGdJQcjH GdENHGQis - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdLhO hGdcQe hHYO aEfc SCdJfi Yf eYfi bhdge YbO GdhVY hYbO GdMed hYf GdJQGcjH GdJbjjOi hGdJQcjH GdENHGQi , aGYde hdOi (B_ (3HGQc Gddg Gddg ajc hdce hfhQ bdhHce HCfhGQ eYQaJg s
(3BNQgG (B:s
(3hdG jSJdRe Pdc Cf jchf NGQLkG Yf eLehY GdeVGa hGdeVGa Edjg , cja hgh LRA ef GdeLehY hGdLRA dGjNQL Yf cdg VQhQg GfJgi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs